The E-govqual and Importance Performance Analysis (IPA) Models Analysis: Review a Web Service Quality of E-government - Yuhefizar, Y.; Utami, Devi; Sudiman, Josephine (JOIV : International Journal on Informatics Visualization, 2024)
The e-government web portal serves as a crucial platform for providing information that can be easily and universally accessed. This serves as an intermediary between the municipal administration and the community, ultimately resulting in improved and streamlined public services. Several variables, including age and proficiency in using the integrated system, provide insights on how to gauge user satisfaction levels of the information system and its current users. The e-govqual and Importance Performance Analysis (IPA) models are accurate indicators of user satisfaction. This article seeks to understand the perception of users of the e-government web portal of the municipal Tanah Datar municipality. It aims to compare the servqual and the IPA model to determine the most suitable method for assessing public perceptions and identifying priority attributes to improve service quality. These two approaches share the same objective, but employ different methodologies. The user's perception of performance is designated as the independent variable (X) using a quantitative approach, while service quality expectations are designated as the dependent variable (Y). This is achieved by combining the Likert scale with five dimensions. This study uses questionnaires to gather data from 275 participants and uses two models, E-govqual and Importance Performance Analysis (IPA), to assess user satisfaction. The findings indicate that it is crucial for the government to respond quickly to user issues, provide feedback on user input, and regularly update the material on the Web portal.